If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(t-3)+3t=6(2t+2)-10
We move all terms to the left:
9(t-3)+3t-(6(2t+2)-10)=0
We add all the numbers together, and all the variables
3t+9(t-3)-(6(2t+2)-10)=0
We multiply parentheses
3t+9t-(6(2t+2)-10)-27=0
We calculate terms in parentheses: -(6(2t+2)-10), so:We add all the numbers together, and all the variables
6(2t+2)-10
We multiply parentheses
12t+12-10
We add all the numbers together, and all the variables
12t+2
Back to the equation:
-(12t+2)
12t-(12t+2)-27=0
We get rid of parentheses
12t-12t-2-27=0
We add all the numbers together, and all the variables
-29!=0
There is no solution for this equation
| 6y+2=3y | | -2x-10=x+14 | | 2^(x+1)=17.2^x-2 | | 2-2y+3(1)=7 | | 3x+12=6x+23 | | 6x+104=16x+-114 | | v²+30=-11v | | 25a²=9 | | 27100=12500(1+0,35)n | | 25a²=19 | | 3/8x+2=5/12-4x | | -6(1-8b=-246 | | 25a²+5=14 | | 8(t-4)+4t=4(3t+4)-12 | | 14x+5=69 | | 4(8^(8^x)=-11(8^4x)+20 | | 5+7x-4=9x+33-6x | | -2×+4z=2.16 | | x^2-60=6x | | 36/30=n/5 | | x-36=-23+47 | | 15x^2-x+84=0 | | 3(x-6)=6x+24. | | x/3+3/3=15/4 | | -2.3y=-0.7y+4.8 | | 2+19p-24=-22 | | t^2+13t+8=0 | | x-14=52-21 | | x^2-7.46x-45=0 | | x^2=7.46x-45=0 | | 24x=2980 | | 4/3x+7/6x=48/9 |